The DIAPH3 linker specifies a β-actin network that maintains RhoA and Myosin-II at the cytokinetic furrow - Riya Shah; Thomas C. Panagiotou; Gregory B. Cole; Trevor F. Moraes; Brigitte D. Lavoie; Christopher A. McCulloch; Andrew Wilde (Nature Communications)
Abstract Cytokinesis is the final step of the cell division cycle that leads to the formation of two new cells. Successful cytokinesis requires significant remodelling of the plasma membrane by spatially distinct β- and γ-actin networks. These networks are generated by the formin family of actin nucleators, DIAPH3 and DIAPH1 respectively. Here we show that β- and γ-actin perform specialized and non-redundant roles in cytokinesis and cannot substitute for one another. Expression of hybrid DIAPH1 and DIAPH3 proteins with altered actin isoform specificity relocalized cytokinetic actin isoform networks within the cell, causing cytokinetic failure. Consistent with this we show that β-actin networks, but not γ-actin networks, are required for the maintenance of non-muscle myosin II and RhoA at the cytokinetic furrow. These data suggest that independent and spatially distinct actin isoform networks form scaffolds of unique interactors that facilitate localized biochemical activities to ensure successful cell division.